Comprehensive evaluation of hyperbaric oxygen therapy: Mechanisms, applications, and clinical implications - Silva, Luciano Barreto; Dos Santos, Pedro Guimarães Sampaio Trajano; Ribeiro, Adriana da Costa; Travassos, Rosana Maria Coelho; Ataíde, Juliana Perez Leyva; Guimarães, Lorena Gomes; de Gouveia, Ágatha Nicole Siqueira; Júnior, Paulo Maurício de Reis Melo (LUMEN ET VIRTUS, 2024)
The aim of this work was to conduct a literature review encompassing the fundamental aspects of hyperbaric oxygen therapy (HBOT), including its basic principles, chamber types, and physiological mechanisms. This review outlines the different types of hyperbaric chambers, such as monoplace and multiplace chambers, detailing their design, operational requirements, and specific therapeutic uses. It explores the physiological mechanisms induced by HBOT, including its effects on partial pressure of gases, volumetric changes, and solubility, as well as biochemical and cellular impacts. The review also addresses the therapeutic indications of HBOT, such as its application in treating decompression sickness, gas embolism, and chronic wounds, alongside its limitations and contraindications. It evaluates the advantages and disadvantages of HBOT, highlighting the potential for complications such as barotrauma and oxygen toxicity. Emphasis is placed on the need for careful patient selection and adherence to treatment protocols to optimize outcomes and mitigate risks.